The Evolution of Data-Information-Knowledge-Wisdom in Nursing Informatics. (January 2016) - Ronquillo, Charlene; Currie, Leanne M.; Rodney, Paddy
Abstract : The data-information-knowledge-wisdom (DIKW) model has been widely adopted in nursing informatics. In this article, we examine the evolution of DIKW in nursing informatics while incorporating critiques from other disciplines. This includes examination of assumptions of linearity and hierarchy and an exploration of the implicit philosophical grounding of the model. Two guiding questions are considered: (1) Does DIKW serve clinical information systems, nurses, or both? and (2) What level of theory does DIKW occupy? The DIKW model has been valuable in advancing the independent field of nursing informatics. We offer that if the model is to continue to move forward, its role and functions must be explicitly addressed. Abstract : This article presents an examination of assumptions of linearity and hierarchy, and an exploration of the implicit philosophical grounding of the data-information-knowledge-wisdom (DIKW) model. Two guiding questions are considered: 1) Does DIKW serve clinical information systems, nurses, or both? and 2) What level of theory does DIKW occupy? The DIKW model has been valuable in advancing the independent field of nursing informatics. We offer that if the model is to continue to move forward, its role and functions must be explicitly addressed.